Metcalfa pruinosa (Say) (Auchenorrhyncha Flatidae) infestation in the province of Piacenza (Emilia-Romagna) (Bollettino di zoologia agraria e bachicoltura, 2024)
The occurrence of Metcalfa pruinosa (Say) in the province of Piacenza (Emilia-Romagna) is reported.The first observed presence was in 1985 near an ornamental plant nursery. Afterwards the attacks became widespread in spontaneous vegetation, on grape and peach.
Keywords: Metcalfa pruinosa; North Italy; distribution